Theoretical Aspects of Growth in Developing Countries : External Debt Dynamics and the Role of Human Capital. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper formulates a simple aggregate growth model that is capable of assessing the impact of macroeconomic policies on the long-term performance of a developing country. The model emphasizes expenditures on human capital and the dynamics of external debt, and yields empirically testable hypotheses on the relative importance of various determinants of long-term growth performance. The analytical results suggest a number of implications that are relevant to the design of growth-oriented adjustment programs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet